Spatial–temporal distribution of chikungunya virus in Brazil: a review on the circulating viral genotypes and Aedes (Stegomyia) albopictus as a potential vector - Resck, Maria Eduarda Barreto; Câmara, Daniel Cardoso Portela; dos Santos, Flávia Barreto; dos Santos, Jefferson Pereira Caldas; Alto, Barry Wilmer; Honório, Nildimar Alves (Frontiers in Public Health, 2024)
Chikungunya virus (CHIKV) is mainly transmitted by the invasive mosquito Aedes (Stegomyia) aegypti in tropical and subtropical regions worldwide. However, genetic adaptations of the virus to the peri domestic mosquito vector Aedes (Stegomyia) albopictus has resulted in enhanced vector competence and associated epidemics and may contribute to further geographic expansion of CHIKV. However, evidence-based data on the relative role of Ae. albopictus in CHIKV transmission dynamics are scarce, especially in regions where Ae. aegypti is the main vector, such as in Brazil. Here, we review the CHIKV genotypes circulating in Brazil, spatial and temporal distribution of Chikungunya cases in Brazil, and susceptibility to infection and transmission (i.e., vector competence) of Ae. albopictus for CHIKV to better understand its relative contribution to the virus transmission dynamics.